VCI evaluation by electrochemical impedance spectroscopy - Pinto, E. M. [UNESP]; Âtngelo, A. C.D. [UNESP]; Genovez, M. C. (My University, 2001)
Volatile Corrosion Inhibitors (VCIs) represent a real improvement in the inhibition of corrosion process for metallic materials. However, the evaluation of this class of inhibitors still remains complex and non-reproducible. This paper proposes the use of the electrosorption phenomenon to evaluate the action of VCI in aqueous solution by electrochemical impedance spectroscopy. Charge transfer resistance and electrode capacitance were impedance parameters used to evaluate the inhibition process of mild steel corrosion in NaC1 solution. From the obtained results it was concluded that diethylethanolamine caprilate conferred the best inhibitory performance due to the dense coverage of the adsorbed film on the metallic surface.